Al-Takâmul wa al-Tawfîq bayna al-Fiqh wa al-Tasawwuf: Wijhah Nazhar Kiyahî Muhammad Shâlih Darat al-Samarânî fi Taqaddum al-Fikr al-Dinî fî Indûnîsiyâ - Abdurrohman Kasdi; Umma Farida; Fauzan Adim (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2023)
This article aimed to analyze the perspective of Kiyahî Shâlih Darat in integrating fiqh and Sufism which are generally considered different from one another. Fiqh tends to illustrate the outward side in deriving legal rulings from the Qur’an and Sunnah, while Sufism tends to refer to the inner side in applying the teachings. The integration between both is deemed necessary to balance the internal and external dimensions of Muslim life, as they are an inseparable unit. This research is a qualitative library one with the data collected from the books of Kiyahî Shâlih Darat and research on his ideas. It is furthermore a study that attempts to analyze the contents of Kiyahî Shâlih Dârât’s thought objectively and scientifically to find its meanings and values. The results showed that the Kiyahî Shâlih Darat mastered various disciplines ranging from fiqh, Sufism, tafseer to hadith. His thought reflects the manifestation of a perfect religious intellectual spirit. He interpreted the Islamic teaching and its ritual practices in the context of carrying out the integration between fiqh which emphasized the outward aspects and sufism which focused on the inner ones. According to him, Muslims who only rely on one of both and ignore another cannot be considered perfect Muslims because Islam does not only give attention to external things but also internal ones. Likewise, Islam not only regulates the soul but also takes care of physical matters. Fiqh without Sufism, as he mentioned, will be empty, while Sufism without fiqh will be futile so real Islam is a combination between both.